Assessing the ecotourism carrying capacity and other limits of acceptable change for ecotourism development planning and management the case of the Municipality of Plaridel, Quezon province, Philippines - Rossetti, Isabela Braz; Magnaye, Dina C. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2024)
The coastal municipality of Plaridel in Quezon Province exhibits strong potential for local ecotourism development as highlighted in various local plans and project proposals. One proposed ecotourism circuit in Barangay Ilosong features several nature-based attractions. However, the absence of dedicated ecotourism and management plans in the municipality leaves these sites in Barangay Ilosong vulnerable to the negative impacts of unregulated and unmonitored visitation. Given these circumstances, the study aims to identify the most appropriate ecotourism management measures for Barangay llosong through ecotourism carrying capacity estimation and the Limits of Acceptable Change (LAC) framework, supplemented by site potential evaluation and local policy analysis.

Findings indicate that Barangay Ilosong has significant potential for ecotourism development, particularly through the development of an eco-circuit encompassing Mt. Kiling, Kawa Kawa Falls, Himpoporo Falls, and Ilosong Cave. However, visitation must be accompanied by the implementation of appropriate regulatory and management measures to control use levels and minimize environmental impacts. Based on visitation records, the carrying capacities of the selected sites have generally remained within limits, except for Mt. Kiling and the Kawa Kawa Falls, which have already exceeded the ideal number of visitors per recreational period.

The application of the LAC framework highlights that, within the domain of ecotourism development, maintaining desired ecotourism conditions necessitates complementary efforts for environmental preservation and visitor experience management.

Overall, the current regulatory framework of the Municipality of Plaridel is progressively aligning further with the promotion of ecotourism development in Barangay Ilosong. Nonetheless, the formulation of specific plans, such as the Ecotourism Management Plan, Tourism Development Plan, Solid Waste Management Plan, and Protected Area Management Plan, remains essential to support sustainable ecotourism development.
Thesis
Keywords: Ecotourism -- Philippines -- Plaridel (Quezon).; Sustainable tourism -- Philippines -- Plaridel (Quezon).; Tourism -- Philippines -- Plaridel (Quezon).